Early changes of left atrial function in chronic asymptomatic alcoholics by two-dimensional speckle-tracking echocardiography. Issue 1 (2nd January 2017) - Xu, Rui; Luo, Runlan; Tan, Bijun; Gan, Tian; Li, Guangsen
Abstract : Background Chronic excessive alcohol intake has been reported as a possible cause of dilated cardiomyopathy. Two-dimensional speckle-tracking echocardiography (2D-STE) is a novel method for the angle-independent and objective quantification of myocardial deformation. This study sought to assess left atrial function changes among alcoholics related to the duration of heavy drinking by 2D-STE. Methods We classified 92 asymptomatic alcoholics into mild, moderate and severe groups. Thirty age-matched controls were also recruited. We measured left atrial (LA) phasic volumes (max, min and pre-atrial contraction volume) using Simpson's method in apical four-chamber view. Passive emptying (LAPEF) and active emptying (LAAEF) indices were calculated. Global longitudinal strain rate (SRs) during left ventricular (LV) ejection, early diastolic strain rate (SRe) during LV early diastole and peak negative strain rate (SRa) after the P- wave were also obtained by averaging all atrial segments. Results The alcoholics had larger LA volumes (max, min and pre-atrial contraction volume) since moderate stage ( P < 0.01). LAPEF, SRs SRe, and E/A ratio showed progressive decrease according to the grades of alcoholism. The differences between the groups were significant, beginning from the moderate group ( P < 0.01). During LAAEF, SRa values increased with the disease severity up to moderate alcoholics and then deteriorated significantly in severe alcoholics ( P < 0.01). Conclusions These data suggest that 2D-STE may be considered a promising tool for the early detection of impairment of LA function in alcoholics.